Peran Guru dalam Mendesain Fisik Ruang Kelas di Kelas V SDN Wonosuko 1 Bondowoso - Amalia Dwi Nurhalisah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The background of this research is based on the monotonous nature of classroom layout. The purpose of this study is to determine the role of teachers in designing the physical classroom space in fifth-grade elementary schools. Data collection was conducted in the even semester of the 2025/2026 academic year with fifth-grade students of SDN Wonosuko 1 Bondowoso as the subjects. The instruments used included observation guidelines, interview guides, and documentation. The observation results showed that students felt more comfortable with the new classroom layout. In addition, this layout can also encourage learning motivation and potentially improve student learning outcomes. Based on data analysis, it can be concluded that there is a positive influence of the physical classroom design layout on student comfort and learning motivation.
Finalisasi 9 Juli 2026_Yudi
Keywords: Teacher role; classroom design; learning comfort; learning motivation